Acute IL-1RA treatment suppresses the peripheral and central inflammatory response to spinal cord injury - Yates, AG; Jogia, T; Gillespie, ER; Couch, Y; Ruitenberg, MJ; Anthony, DC (BioMed Central, 2021)
Background The acute phase response (APR) to CNS insults contributes to the overall magnitude and nature of the systemic inflammatory response. Aspects of this response are thought to drive secondary inflammatory pathology at the lesion site, and suppression of the APR can therefore afford some neuroprotection. In this study, we examined the APR in a mouse model of traumatic spinal cord injury (SCI), along with its relationship to neutrophil recruitment during the immediate aftermath of the insult. We specifically investigated the effect of IL-1 receptor antagonist (IL-1RA) administration on the APR and leukocyte recruitment to the injured spinal cord.